2017
DOI: 10.1248/cpb.c16-00699
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel Tetramethylpyrazine Derivatives as Potential Neuroprotective Agents

Abstract: Oxidative stress plays a crucial role in neurological diseases, resulting in excessive production of reactive oxygen species, mitochondrial dysfunction and cell death. In this work, we designed and synthesized a series of tetramethylpyrazine (TMP) derivatives and investigated their abilities for scavenging free radicals and preventing against oxidative stress-induced neuronal damage in vitro. Among them, compound 22a, consisted of TMP, caffeic acid and a nitrone group, showed potent radical-scavenging activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…However, a high concentration of extracellular glutamate is toxic to nerve cells and is considered to be a key contributor in the pathogenesis of neurodegenerative diseases such as ischemic stroke ( Wahl et al, 1994 ). In our previous study, we reported that compound 22a exhibited neuroprotective effects against oxidative stress-induced neuronal loss in vitro and protected against ischemic stroke in vivo ( Chen et al, 2017 ). However, the exact mechanisms underlying the neuroprotection of compound 22a is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a high concentration of extracellular glutamate is toxic to nerve cells and is considered to be a key contributor in the pathogenesis of neurodegenerative diseases such as ischemic stroke ( Wahl et al, 1994 ). In our previous study, we reported that compound 22a exhibited neuroprotective effects against oxidative stress-induced neuronal loss in vitro and protected against ischemic stroke in vivo ( Chen et al, 2017 ). However, the exact mechanisms underlying the neuroprotection of compound 22a is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, a TMP-derived compound 22a was designed to combine caffeic acid ( Touaibia et al, 2011 ) (another natural compound with versatile pharmacological activities) and a nitrone group ( Floyd et al, 2013 ) (a strong free radical-trapping agent) with TMP. We found that compound 22a exhibited strong ROS scavenging activity and exerted protective effects in models of ischemic stroke in vivo ( Chen et al, 2017 ). In the present study, the neuroprotective effects of compound 22a against glutamate-induced excitotoxicity on primary culture of rat CGNs, and the underlying mechanisms of action, were further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…reported the synthesis of a similar series of tetramethylpyrazine derivatives and investigated their activity in prevention against oxidative stress‐induced neuronal damage and scavenging free radicals in vitro. They discovered some compounds to be potential neuroprotective agents in neurological diseases treatment . Xu and coworkers also synthesized a derivative of TMP that showed protective effect in excitotoxicity‐challenged cerebellar granule neurons model and exhibited prodifferential effect, which rendered this compound to be a multitarget drug candidate for AD therapy principally ischemic stroke…”
Section: Resultsmentioning
confidence: 99%
“…Caffeic acid , a hydroxyl extractive of cinnamic acid possessing a phenolic moiety ( 44 ), and its ester derivatives show excellent neuroprotection ( 45 ). The chemical combination of TBN and caffeic acid is compound 22a, which maintains mitochondrial membrane potential and inhibits cell apoptosis by activating the PI3K/AKT/GSK3β pathway, thereby protecting against glutamate-induced cerebellar granule neuronal damage ( 46 , 47 ). The compound 7,9(11),22-ergostatrien-3β-ol (EK-100) is the main active component extracted from the ethyl acetate crude extract of Antrodia Camphorate (Aphyllophorales, Niu-Zhang-Zhi in Chinese) (EtOAc-AC), a well-known TCM ( 48 ).…”
Section: Active Extracts Of Chinese Medicinesmentioning
confidence: 99%
“…Compound 22a and Senkyunolide-H, are derived from Ligusticum wallichii. Both maintains mitochondrial membrane potential, inhibits cell apoptosis and inflammatory factor release by activating the PI3K/AKT pathways ( 46 , 47 , 86 ). Extracted from Scutellaria baicalensis Georgi, Baicalein and Baicalin inhibits autophagy, reduces cerebral infarction and neuronal loss via activation of the PI3K/AKT mediated pathway ( 25 , 109 ).…”
Section: Conclusion and Prospectmentioning
confidence: 99%